Effects of Funding Portfolios on the Credit Supply of Canadian Banks - H. Evren Damar; Césaire A. Meh; Yaz Terajima (Bank of Canada, 2015)
This paper studies how banks simultaneously manage the two sides of their balance sheet and its implications for bank risk taking and real economic activity. First, we analyze how changes in funding affect the supply of bank loans. We then examine how the supply of credit by banks that rely more on wholesale funding changed during periods of lowfor- long interest rates and during the recent financial crisis. The findings suggest that contemporaneous changes in wholesale funding are positively associated with large business loans. In addition, we find that banks that rely on wholesale funding tend to increase mortgage loans in a prolonged low rate environment. This is suggestive evidence that these banks may be taking on more liquidity risk by supplying long-term loans with short-term funding. We also find that mortgage lending by banks relying more on wholesale funding increased, a likely result of government policies to increase liquidity in the market during the crisis.
Keywords: E52; G21; 330; Financial institutions; Financial stability; Financial system regulation and policies; Monetary policy implementation